Chemical reaction and radiation effect on boundary layer Maxwell-nanofluid flow past over a stretching sheet with slips: Non-flick and non-Fourier laws - B․Shankar Goud; N. Amar; K Srihari; D. Venkateshwar Rao; Thadakamalla Srinivasulu (Partial Differential Equations in Applied Mathematics, 2025)
The purpose of this research is to look at the phenomenon of a Maxwell nanofluid slip flow caused by a stretched sheet passing through a porous material with a magnetic field. Additionally, the concepts of radiation, Brownian motion, and thermophoresis with slip consequences have been presented. The dimensionless version of the governing equations is obtained and by applying the correct similarity conversion, the main PDEs are rebuilt into nonlinear ordinary differential equations. To establish numerical solutions for this examination, the dimensionless equations were numerically solved utilizing the bvp4c scheme, which is an inherent solver in MATLAB. The primary emphasis of the current investigation is on the investigation of significant factors that are associated with the governing equations and the effects that these parameters have on flow fields. The main finding of this study is that velocity increases with an increase in the Maxwell parameter. Furthermore, the temperature and concentration gradients are reduced when the heat and flux relaxation time parameters increase. Maxwell fluids are used in a variety of real-world applications, including biomedical engineering, the food industry, polymer processing, civil engineering, the automotive industry, and others.